The Internationalization of “West Papua” Issue and Its Impact on Indonesia’s Policy to the South Pacific Region - Floranesia Lantang; Edwin M.B Tambunan (JAS (Journal of ASEAN Studies), 2020)
This research argues that the internationalization of "West Papua" issue through social media has contributed to a shift of Indonesia's policy to the South Pacific region from ignorance to initiative approach. Underlying this argument is a growing concern of Indonesia regarding the use of social media by Papuan pro-independence activists that resulted to the increasing awareness and support towards the independence of West Papua from Pacific countries as human rights problems become the highlight of West Papua’s issue. The method used in this research was qualitative research method focusing on descriptive analysis of the internationalization of West Papua issue on social media. This research results show that initiative approach from Indonesia is merely narrowing the gap of the issue instead of reducing the internationalization of the West Papua issue.